Analisis Keuangan Kelayakan Bisnis Syariah Hamdi's Model (Studi Kasus Usaha Swalayan Syariah Di Pekanbaru) - Hamdi Agustin (Forum Manajemen Indonesia (FMI), 2017)
The purporse this studies to calculation of financial analysis on the feasibility of investments the Hamdi’s Model on Islamic concepts.. In this study try to do research as the implications of this concept and examples of cases in the supermarket to enrich financial research that will find a new concept in the field of Islamic financial analysis business feasibility study. The result of reseach of the financial aspects of the show that a analysis of the feasibility study that takes in the decision to accept or reject by using Hamdi’s model. This analysis shows the calculation Hamdi’s model could be used in assessing the feasibility of investing can be used in the Islamic feasible study anayisis. The method of syariah are calculation Gold Value Method (GVM), Methods Gold Index (GI) and methods Investible Surplus Analysis Method. Keywords : Feasible study, syariah method and Gold Value Method